Profile of Primary Angle Closure Disease - singh, Rajyeshwar; gupta, manisha; Gupta, Priyanka (Student's Journal of Health Research Africa, 2025)
Background Glaucoma is the second most common cause of visual morbidity after Cataract. The purpose of the study is to assess the demographic and clinical profile of Primary Angle Closure Disease (PACD) and to evaluate the risk factors associated. Method A prospective observational study including 97 eyes of 50 patients above 40 years, with PACD at a tertiary health care centre. Aphakia, Pseudophakia, previous ocular surgery, secondary glaucoma, and ocular pathology subjects were excluded. Detailed glaucoma workup, slit-lamp examination (VH Grading), Gonioscopy, ocular biometry (Axial Length, Anterior chamber depth, lens thickness) were recorded. All patients diagnosed with PACD were prospectively categorized into three subgroups, namely Primary Angle Closure suspect (PACS), Primary Angle Closure (PAC), and Primary Angle Closure Glaucoma (PACG) using International Society of Geographical and Epidemiological Ophthalmology (ISGEO) Classification. Results Out of 50 subjects, 52% were males, and 58% urban residents. Mean age was 60.14±11.81 years in PACD. Out of the total 97 eyes, 39.2% (38 eyes) had PACS subtype, 38.1% (37 eyes) had PAC, and 22.7% (22 eyes) had PACG subtype. The mean standard value of axial length was22.03±0.62mm in PACS, 22.46±0.42mm in PAC & 22.41±0.71mm in PACG. Anterior chamber depth was 2.36±0.21mm in PACS, 2.33±0.12mm in PAC & 2.22±0.7mm in PACG subgroup. Lens thickness was 4.52±0.74mm in PACS, 4.54±1.07mm in PAC & 4.61±1.05mm in PACG subgroup. Conclusion PACS was the most common subgroup. Shallow anterior chamber, increased lens thickness, lesser axial length, and advancing age were the risk factors in PACD. Recommendations The present study highlights that screening of subjects can detect PACD at early stages and thus prevent potential blindness.